Formulating The Strategy In Managing Manufacturing Complexity - Wan Mahmood, Wan Hasrulnizzam; Mohd Rosdi, Mohd Noor Hanif; Mohd Razali, Muhamad (Publications International Lahore, Pakistan, 2014)
This paper proposed a framework formulating the strategy in managing manufacturing complexities which are divided into two main categories: production strategy and human management. The sub categories for production strategy are manufacturing area, scheduling management and supply chain management; while for human management are self-assessment and organizations’ transformation. There are a lot more elements under these sub categories. Each sub category is related with each other where manufacturing activities involved all of them. The conceptual framework initiated in this paper is able to provide general guidance for manufacturer to manage any sort of manufacturing complexity appeared during their manufacturing activities works or personnel to take action after determining the manufacturing complexity areas and components around their routine activities.